Effects of Pharmacist-Conducted Medication Reconciliation at Discharge on 30-Day Readmission Rates of Patients With Chronic Obstructive Pulmonary Disease. (June 2021) - Singh, Divita; Fahim, Germin; Ghin, Hoytin Lee; Mathis, Scott
Purpose: To analyze effect of pharmacist-conducted medication reconciliation on 30-day readmission rates in chronic obstructive pulmonary disease (COPD) and identify common medication errors among patient with readmissions. Methods: Pharmacists were educated on discharge medication reconciliation for patients with COPD. A retrospective chart review was conducted on patients who underwent pharmacist-conducted discharge medication reconciliation to determine 30-day readmissions. Medication errors analyzed included medication omissions and dose or frequency errors. Previously collected internal research without pharmacist-conducted medication reconciliation served as the control. Results: There were 65 patients in the control group and 50 in the intervention group. About 25% of patients in the control group and 26% of patients in the intervention group had any cause readmissions within 30 days of discharge ( P = .87). Both the control and the intervention group had similar COPD-related readmissions of 12.3% and 12.6%, respectively. Medication dose or frequency errors consisted of 68.9% and 46.7% of total errors in the control and the intervention groups, respectively. Long-acting muscarinic antagonist (LAMA) or long-acting beta 2-agonist (LABA) were the most common drug classes to be incorrectly dosed or omitted at discharge. In the intervention group, 30 errors were identified. Due to inability to coordinate discharges, pharmacists intervened on 13 errors, 7 of which were accepted by the prescriber. Conclusion: Pharmacist-conducted medication reconciliation at discharge did not affect 30-day readmission rates of patients with COPD. Confounding factors included a small sample size, passive pharmacist education, and discharge issues. The most common medication errors at discharge were dosing or frequency errors of LABAs or LAMAs.